2017
DOI: 10.1177/1055665617732854
|View full text |Cite
|
Sign up to set email alerts
|

What Matters to Patients With Cleft Lip and/or Palate

Abstract: A conceptual framework of concepts of interest to individuals with CL/P formed the basis of the scales in the CLEFT-Q. Each subdomain represents an independently functioning scale. Understanding what matters to patients is essential in guiding PRO measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 31 publications
2
41
1
1
Order By: Relevance
“…The literature showed that appearance and speech were the most frequently discussed points for children with facial clefts. Individuals with facial clefts may struggle with the psychological and social sequels of having differences in their appearance and speech [28].…”
Section: Discussionmentioning
confidence: 99%
“…The literature showed that appearance and speech were the most frequently discussed points for children with facial clefts. Individuals with facial clefts may struggle with the psychological and social sequels of having differences in their appearance and speech [28].…”
Section: Discussionmentioning
confidence: 99%
“…The CLEFT-Q has been validated for patients aged between 6 and 29 years in different countries in North America, Europe, and Asia (Tsangaris et al, 2017a; Wong Riff et al, 2017). It consists of a total of 171 items, divided into 13 scales, evaluating the appearance, health-related quality of life, and facial function and each subdomain represents an independently functioning scale (Wong Riff et al, 2018; Table 2). Normative values of this rigorously developed instrument have recently been published, in addition to the translation and cultural adaptation of the CLEFT-Q to 3 Spanish language varieties (Tsangaris et al, 2017b; Klassen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…CLEFT-Q was developed as a CL/P specific questionnaire through a process of review of existing PROMs in the field ( Klassen et al, 2012 ), by qualitative research of patients with CL/P from different countries ( Tsangaris et al, 2017 ; Wong Riff et al, 2018 ), field testing in 12 countries and, finally, analysis with Rasch measurement theory ( Klassen et al, 2018b ). It consists of 12 scales and 1 checklist with 6 to 12 items each.…”
Section: Methodsmentioning
confidence: 99%